In nobody's backyard : Maurice Bishop's speeches, 1979-1983 : a memorial volume; introduction by Richard Hart - Bishop, Maurice (Zed Books LondonGB, 1984)
Presents the speeches made by Maurice Bishop in his capacity as Prime Minister of Grenada and leader of the New Jewel Movement, the revolutionary party.